TÌM ĐIỀU KIỆN ĐỂ BIỂU THỨC TRONG CĂN BẬC 2 CÓ NGHĨA
1/\(\sqrt{\dfrac{2x-3}{2x^2+1}}\)
2/\(\sqrt{-2x+3}\)
3/\(\sqrt{-7x-14}\)
4/\(\sqrt{\dfrac{x^2+2}{1-4x}}\)
5/\(\sqrt{-5-3x}\)
Tìm x ?
a. 3x^3 + 2x = 2căn (x^2+7x+7)
b. (x+5)(2-x) = 3căn (x^2+3x)
c. x/(x+1) - 2căn (x+1/x) =3
4) |3 - 2x| = x + 2
5) |2x - 1| = 5 - x
6) |- 3x| = x - 2
7) |2 - 3x| = 2x + 1
8) |2x - 1| + |4x ^ 2 - 1| = 0
9) (2x + 5)/(x + 3) + 1 = 4/(x ^ 2 + 2x - 3) - (3x - 1)/(1 - x)
10) (x - 1)/(x + 3) - x/(x - 3) = (7x - 3)/(9 - x ^ 2)
11) 5 + 96/(x ^ 2 - 16) = (2x - 1)/(x + 4) + (3x - 1)/(x - 4)
12) (2x)/(2x - 1) + x/(2x + 1) = 1 + 4/((2x - 1)(2x + 1))
13) (x + 2)/(x - 2) - 1/x = 2/(x ^ 2 - 2x)
14) x/(2x - 6) + x/(2x + 2) = (2x + 4)/(x ^ 2 - 2x - 3)
1)\(7\sqrt{3x-7}+\left(4x-7\right)\sqrt{7-x}=32\)
2)\(4x^2-11x+6=\left(x-1\right)\sqrt{2x^2-6x+6}\)
3)\(9+3\sqrt{x\left(3-2x\right)}=7\sqrt{x}+5\sqrt{3-2x}\)
4)\(\sqrt{2x^2+4x+7}=x^4+4x^3+3x^2-2x-7\)
5)\(\frac{6-2x}{\sqrt{5-x}}+\frac{6+2x}{\sqrt{5+x}}=\frac{8}{3}\)
6)\(2\left(5x-3\right)\sqrt{x+1}+\left(x+1\right)\sqrt{3-x}=3\left(5x+1\right)\)
7)\(\sqrt{7x+7}+\sqrt{7x-6}+2\sqrt{49x^2+7x-42}=181-14x\)
giải phương trình:
\(a,\sqrt{2x-3}+\sqrt{5-2x}=3x^2-12x+14\)
\(b,x^2-2x-x\sqrt{x}-2\sqrt{x}+4=0\)
\(c,3x^2+21x+18+2\sqrt{x^2+7x+7}=2\)
\(d,\frac{2\sqrt{2}}{\sqrt{x+1}}+\sqrt{x}=\sqrt{x+9}\)
\(c,\sqrt{3x^2-5x+1}-\sqrt{x^2-2}=\sqrt{3\left(x^2-x-1\right)}-\sqrt{x^2-3x+4}\)
giải các pt sau
a. 50-3x(15-2x)=6x2+5x-200
b. 8x3+1=(2x+1)(5-2x)
c. x-1+ lx-1l + lx+2l
d. (x2+3x+2)(x2+7x+12)=24
e. (2x-1)3+(x-1)3+(2-3x)3=0
f. (x+3)4+(x-1)4=626
tìm x biết a (x-2)^2+(x+3)^2-4(x+1)=5
b (2x-3)(2x+3)-(x-1)^2-3x(x-5)=-44
c (5x+1)^2-(5x+3)(5x-3)=30
d (x+3)^2+(x-2)(x+2)-2(x-1)^2=7
1) |2x - 1| = 5
2) |2x - 1| = |x + 5|
3) |3x + 1| = x - 2
4) |3 - 2x| = x + 2
5) |2x - 1| = 5 - x
6) |- 3x| = x - 2
7) |2 - 3x| = 2x + 1
8) |2x - 1| + |4x ^ 2 - 1| = 0
9) (2x + 5)/(x + 3) + 1 = 4/(x ^ 2 + 2x - 3) - (3x - 1)/(1 - x)
10) (x - 1)/(x + 3) - x/(x - 3) = (7x - 3)/(9 - x ^ 2)
11) 5 + 96/(x ^ 2 - 16) = (2x - 1)/(x + 4) + (3x - 1)/(x - 4)
12) (2x)/(2x - 1) + x/(2x + 1) = 1 + 4/((2x - 1)(2x + 1))
13) (x + 2)/(x - 2) - 1/x = 2/(x ^ 2 - 2x)
14) x/(2x - 6) + x/(2x + 2) = (2x + 4)/(x ^ 2 - 2x - 3)